2020
DOI: 10.1152/ajpheart.00657.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cigarette smoke exposure triggers a vicious cycle of leukocyte and endothelial-mediated oxidant stress that results in vascular dysfunction

Abstract: In a chronic model of smoking-induced cardiovascular disease, we define underlying mechanisms of smoking-induced vascular endothelial dysfunction (VED). Smoking exposure triggered VED and hypertension and led to vascular macrophage infiltration with concomitant increase in superoxide and NADPH oxidase levels as early as 16 wk of exposure. This oxidative stress was accompanied by tetrahydrobiopterin depletion, resulting in endothelial nitric oxide synthase uncoupling with further superoxide generation triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…The supernatant (0.5 mL) was mixed with 2 mL of 0.3 M disodium hydrogen phosphate buffer (pH 8.4) and 0.4 mL of distilled water. Then, 0.25 mL of 0.001 M freshly prepared DTNB 5 50–dithiobis (2-nitrobenzoic acid) dissolved in 1% w/v sodium citrate] was added to the reaction mixture, and incubated for 10 min. The absorbance of the yellow colored complex was noted spectrophotometrically at 412 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant (0.5 mL) was mixed with 2 mL of 0.3 M disodium hydrogen phosphate buffer (pH 8.4) and 0.4 mL of distilled water. Then, 0.25 mL of 0.001 M freshly prepared DTNB 5 50–dithiobis (2-nitrobenzoic acid) dissolved in 1% w/v sodium citrate] was added to the reaction mixture, and incubated for 10 min. The absorbance of the yellow colored complex was noted spectrophotometrically at 412 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 3 ] Vascular endothelial dysfunction (VED) of microvessels results in reduced activation of endothelial nitric oxide synthase (eNOS), reduced generation and bioavailability of nitric oxide (NO) and increased production of reactive oxygen species (ROS). [ 4 5 ] VED, which is one of the important among the earliest stages has been associated in the pathogenesis of hypertension, coronary artery diseases and nephropathy. [ 6 7 ] A correlation between VED and kidney injury has been demonstrated in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to tobacco smoke impairs the function of vascular endothelial cells, but most of the research focused on coronary arteries. [32][33][34] Further research is needed on the pathogenesis of RAP caused by smoking and whether smoking cessation can reduce the risk of recurrence. Anyway, physicians should be advising patients to quit smoking at all times.…”
mentioning
confidence: 99%
“…It has been suggested that smoke exposure primes leukocytes to promote aortic degradation. Cigarette smoke also activates endothelial cells to express adhesion molecules and chemokines promoting leukocyte infiltration into the aortic wall [ 20 ]. In one mouse study, adoptive transfer of leukocytes from mice exposed to cigarette smoke promoted induction of larger aneurysms in an elastase model [ 21 ].…”
Section: Clinical Risk Factors For Aaa Rupturementioning
confidence: 99%